The complex nature of complexity (in Polish) (Diametros, 2013)
The article presents various notions of complexity: complexity as length of description, algorithmic complexity, complexity as logical depth, complexity as degree of hierarchy, and effective complexity, which is coupled with the theory of complex adaptive systems. In the article I also discuss many problems connected with these notions of complexity and the ontological and epistemological implications of the theory of complexity. The main thesis is that there is no one, general notion of complexity; the context must always be taken into consideration. The program called "complexity science" is also disputable because of the many problems with the laws of complexity and predictions which allow us to speak about "science" in this particular case.
Keywords: complexity; ontology; epistemology; science; philosophy of nature; Bennett; Lloyd; Morin; Simon